Family-focused contextual factors associated with lifestyle patterns in young children from two mother-offspring cohorts: GUSTO and EDEN - Airu Chia; Alexandra Descarpentrie; Rene N. Cheong; Jia Ying Toh; Padmapriya Natarajan; Ray Sugianto; Shirong Cai; Cécilia Saldanha-Gomes; Patricia Dargent-Molina; Blandine de Lauzon-Guillain; Sabine Plancoulaine; Carla Lança; et al. (BMC, 2022)
Abstract Background Integrated patterns of energy balance-related behaviours of preschool children in Asia are sparse, with few comparative analyses. Purpose Using cohorts in Singapore (GUSTO) and France (EDEN), we characterized lifestyle patterns of children and investigated their associations with family-focused contextual factors. Methods Ten behavioural variables related to child's diet, walking, outdoor play and screen time were ascertained by parental questionnaires at age 5-6 years. Using principal component analysis, sex-specific lifestyle patterns were derived independently for 630 GUSTO and 989 EDEN children. Contextual variables were organised into distal (family socio-economics, demographics), intermediate (parental health, lifestyle habits) and proximal (parent-child interaction factors) levels of influence and analysed with hierarchical linear regression. Results Three broadly similar lifestyle patterns were identified in both cohorts: "discretionary consumption and high screen time", "fruit, vegetables, and low screen time" and "high outdoor playtime and walking". The latter two patterns showed small differences between cohorts and sexes. The "discretionary consumption and high screen time" pattern was consistently similar in both cohorts; distal associated factors were lower maternal education (EDEN boys), no younger siblings (GUSTO boys) and Malay/Indian ethnicity (GUSTO), while intermediate and proximal associated factors in both cohorts and sexes were poor maternal diets during pregnancy, parents allowing high child control over food intake, snacking between meals and having television on while eating. Conclusions Three similar lifestyle patterns were observed among preschool children in Singapore and France. There were more common associated proximal factors than distal ones. Cohort specific family-focused contextual factors likely reflect differences in social and cultural settings. Findings will aid development of strategies to improve child health.